Deep eutectic solvent and inorganic salt pretreatment of lignocellulosic biomass for improving xylose recovery. (February 2018) - Loow, Yu-Loong; Wu, Ta Yeong; Yang, Ge Hoa; Ang, Lin Yang; New, Eng Kein; Siow, Lee Fong; Md. Jahim, Jamaliah; Mohammad, Abdul Wahab; Teoh, Wen Hui
Graphical abstract: Highlights: Sequential pretreatment using DES and inorganic salt showed synergistic effect. Overall inhibitor productions were low after undergoing the combined pretreatment. DES was an effective phenolic compound extractor in the solubilization of lignin. The underlying mechanism was studied based on FE-SEM, BET, XRD, and FTIR. Abstract: Deep eutectic solvents (DESs) have received considerable attention in recent years due to their low cost, low toxicity, and biodegradable properties. In this study, a sequential pretreatment comprising of a DES (choline chloride:urea in a ratio of 1:2) and divalent inorganic salt (CuCl2 ) was evaluated, with the aim of recovering xylose from oil palm fronds (OPF). At a solid-to-liquid ratio of 1:10 (w/v), DES alone was ineffective in promoting xylose extraction from OPF. However, a combination of DES (120 °C, 4 h) and 0.4 mol/L of CuCl2 (120 °C, 30 min) resulted in a pretreatment hydrolysate containing 14.76 g/L of xylose, remarkably yielding 25% more xylose than the CuCl2 -only pretreatment (11.87 g/L). Characterization studies such as FE-SEM, BET, XRD, and FTIR confirmed the delignification of OPF when DES was implemented. Thus, the use of this integrated pretreatment system enabled xylose recoveries which were comparable with other traditional pretreatments.